The Analysis of Role of Job Satisfaction and Motivation on Teachers Performance in Integrated Islamic High School - Arifin Arifin; Muhammad Ade Kurnia Harahap; Noor Aziz; Muhammad Nur; Sudadi Pranata (Departement of Mathematics Education, 2023)
This research's objective was to ascertain how motivation and job satisfaction affected every junior high school teacher's performance. The saturated sampling method was used to select 35 teachers for this study. Analysis is conducted using multiple linear regressions. The findings of the study demonstrate that instructors' motivation and job satisfaction significantly affect their performance. At the same time, job happiness and motivation have a significant impact on employee performance.